Brasov 2018: 5th International Conference on Theoretical and Applied Linguistics: Structure, Use, and Meaning - Aplicada a la Comunicación, Círculo de Lingüística (Círculo de Lingüística Aplicada a la Comunicación, 2018)
Brasov 2018: 5th International Conference on Theoretical and Applied Linguistics: Structure, Use, and Meaning